The Effect of Religious Activities on Criminal Thinking in Prisoners of the State Prison Class I Surakarta - Maki Zaenudin Subarkah; Yorram Widyatama (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2022)
Currently, the Class I Rutan in Surakarta has an average over capacity rate of 88.5% over the last 12 months. So the number of officers for 48 inmates. There are various causes that are a factor in the excess capacity in the Class I Rutan Surakarta, including the high crime rate and the fairly high prison sentence. From the existing data, in the city of Surakarta there were 26 recidivists out of 86 people who were involved in drugs in the Class I Rutan Surakarta in 2013, and increased to 38 recidivists from 125 drug offenders in 2014. The purpose of this study was to determine the effect of Religion towards criminal thoughts in inmates of the Class I State Detention Center (Rutan) Surakarta and to determine the level of influence of religious activities on criminal thoughts in the inmates of the Class I State Detention Center (Rutan) Surakarta. The study was conducted using quantitative methods that took a sample of 85 people to be respondents taken from the Surakarta Rutan. To analyze the data, a simple linear regression analysis was performed with the help of SPSS software with a significance level of 10%. From the test results, the correlation coefficient is 0.558 and the coefficient of determination is 0.331. From the significance test, a p value of 0.00 is obtained which is smaller than 0.05 and a value in a negative direction is obtained so that there is a significant and negative influence between Religious Activities on the level of Criminal Thoughts of the inmates of the Class I Rutan in Surakarta with the regression equation Y =99.356 – 0.668X. By knowing the results, it is hoped that it can be used as a reference that these activities can affect the criminal mind. So that efforts can be made for intensive spiritual development to be in accordance with the religion embraced in order to avoid criminal thoughts.